Upaya Peningkatan Hasil Belajar Siswa Kelas 3B SDN Tlogosari Wetan 02 menggunakan Model Pembelajaran Group Investigation Tahun Ajaran Gasal 2021/2022 - Muamanah Muamanah (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The aim of learning mathematics is to form creative and innovative students. To achieve this goal, a Group Investigation (GI) learning model is needed to improve student learning outcomes. The aim of this research is to improve the learning outcomes of class 3B students at SDN Tlogosari Wetan 02 for the Odd school year 2021/2022. The method in this research is Classroom Action Research (PTK). The data collection techniques in this research are written test techniques, observation and documentation. The results of this research were an increase in learning outcomes for class 3B students at SDN Tlogosari Wetan 02 from cycle I, namely that 18 students had achieved the KKM (62.07%) increasing to 25 students in cycle II (86.21%). Based on classical success indicators, because the number of students who reached the KKM (75) was more than 85%, the GI Learning Model was successful in improving student learning outcomes at 3B SDN Tlogosari Wetan 02 for the odd academic year 2021/2022.